The importance of corporate identity in promoting Kota Bharu flying club / Siti Khatijah Mohd Jazan - Mohd Jazan, Siti Khatijah (Faculty of Art and Design, 2013)
The purpose of this research is looking for the importance of corporate identity in promoting Kota Bharu Flying Club. This approach will help the club to get a better identity corporate and able to come out with a good promoting to expose their service.Corporate identity is a system of recognized to club or organisation. It is about perception of the services that are provided. It also can build confidence and pride in the work. The Kota Bharu Flyng Club was established in December 2009 in Collaboration with APFT.The club was set up to being people of all walks of lie to come togehther and share their passsion for flying. Research objective for this club is to give the public the trust and let them know this club can be join or enter by all level of income.This was due to the change of perception among the public that they are not afford to join this.One of the key consuderations in terms of successful branding is the nature of the business,product or service.lt will be important to keep these aspects of the company. Images,colors and even the style of artistry used in any logo or brand image will all prompt customers or potiential clients to make assumptions.Corporate identity branding will give rise to them irrespective and appear vibrant and up to date with their best design or logo. This research is done to find out how far the effectiveness of best design in their corporate identity such as logo and other corporate items for promoting their services. In this research, 50 publics were involved to achieve the objective for this study. In this case, from the research corporate identity is very important on creating positive significance and has a strong identity in the globalizing world of today to well be known organization.